Taxes and traffic in Asian cities: Ownership and use taxes on autos in Singapore - Ngee-Choon Chia; Albert K. C. Tsui; John Whalley (The University of Western Ontario, Department of Economics, 2003)
This paper presents a simple general equilibrium model involving trips from residential areas to a central business district, along with modal choice between cars and public transit. Using a calibrated numerical model, we investigate the relative merits of ownership and use taxes. The proposed model is used to evaluate traffic control policies in Singapore and can be used in other Asian countries. We compare full internalisation of congestion externalities to optimal tax outcomes for the different tax types. In our framework, use taxes restore Pareto optimality since congestion damage rises with more trips. Ownership taxes only partially internalise congestion externalities. However, in terms of revenue-raising ability, the marginal excess burdens in the neighbourhood of optimal taxes are typically lower for ownership taxes than use taxes.
Keywords: H21; H31; R48; 330